Shakespeare, Hamlet - Cantor, Paul A. 1945- (Landmarks of world literature, 2004)
In this useful guide, Paul Cantor provides a clearly structured introduction to Shakespeare's most famous tragedy. Cantor examines Hamlet's status as tragic hero and the central enigma of the delayed revenge in the light of the play's Renaissance context. He offers students a lucid discussion of the dramatic and poetic techniques used in the play. In the final chapter he deals with the uniquely varied reception of Hamlet on the stage and in literature generally from the seventeenth century to the present day